AUGMENTED REALITY FOR PRESCHOOLERS: LEARNING MEDIA TO INTRODUCE SEX EDUCATION - Oktavia Hardiyantari; Soraya Fatmawati (INOPENDAS: Jurnal Ilmiah Kependidikan, 2021)
This study aims to describe how to use Augmented Reality (AR) in introducing sexual education for preschoolers. This AR-based learning media helps provide an interactive and interesting learning experience. In addition, AR-based learning media in the form of flashcards with an application installed on the Andorid-based smartphone supports preschoolers to study their body parts without limitation of time and place. The integration of AR in the learning of preschool children aims to facilitate parents and teachers as the ideal figure to provide sexual education for their children.The method used in this research is descriptive qualitative research method. The data collection technique uses three techniques: interviews, observation, and documentation. The validity of the data was tested using data triangulation techniques and triangulation methods. Data analysis uses a data reduction process flow, data presentation and verification or conclusion.The results showed that through this AR-based media preschooler learned pictures and songs about which parts of the body they should touch, and which should not be touched. The application of this media is not only carried out by teachers at school but also allows it to be used by parents at home. Therefore, parents will contribute actively to introduce sex education to their children.